2023
DOI: 10.3389/feduc.2023.1076249
|View full text |Cite
|
Sign up to set email alerts
|

Hate speech in adolescents: A binational study on prevalence and demographic differences

Abstract: Hate speech, or intentional derogatory expressions about people based on assigned group characteristics, has been studied primarily in online contexts. Less is known about the occurrence of this phenomenon in schools. As it has negative consequences for victims, perpetrators, and those who witness it, it is crucial to characterize the occurrence of offline (i.e., in the school) and online hate speech to describe similarities and differences between these two socialization contexts. The present study aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…In one study among German adolescents, around 65% of the participants reported witnessing hate speech in schools at least once within 12 months (Castellanos, Wettstein, Wachs, Kansok-Dusche, et al, 2023).…”
Section: Bystander Responses To Hate Speechmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study among German adolescents, around 65% of the participants reported witnessing hate speech in schools at least once within 12 months (Castellanos, Wettstein, Wachs, Kansok-Dusche, et al, 2023).…”
Section: Bystander Responses To Hate Speechmentioning
confidence: 99%
“…Hate speech can be defined as any derogatory expression (e.g., words, posts, images, videos) expressed to cause harm to people (directly or vicariously) based on actual or assigned group characteristics (e.g., ethnicity, sexual orientation, religious affiliation; Kansok‐Dusche et al, 2022). The most common targets of hate speech in German schools are people from ethnic minorities and with immigrant background (Castellanos, Wettstein, Wachs, Kansok‐Dusche, et al, 2023). Therefore, we will focus on racist hate speech in this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies support that men score higher than women on social dominance orientation in adulthood (Sidanius et al, 2017; Zubielevitch et al, 2023), this gender difference is not present in childhood and adolescence (Pan et al, 2020; Volk et al, 2021). Furthermore, girls show higher levels of empathy, especially on its affective component (Farrell & Vaillancourt, 2021; Garandeau et al, 2022), lower levels of moral disengagement (Falla et al, 2021), and less frequency of online (Wachs et al, 2021) and offline hate speech perpetration (Castellanos et al, 2023; Kansok‐Dusche et al, 2023). Regarding the association among these characteristics, studies show that boys exhibit stronger associations between social dominance orientation and physical aggression (Gumpel & Gotdiner, 2023), moral disengagement (Gumpel & Gotdiner, 2023), and bullying (Pan et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%